Phase-locking of multiple acoustic resonances by intense optomechanical interactions in a soliton fiber laser - Yeh, Dung Han; He, Wenbin; Pang, Meng; Jiang, Xin; Russell, Philip St. John (Optics InfoBase Conference Papers, 2020)
In a soliton fiber laser incorporating three different PCF sections and optomechanically mode-locked at around 1.94 GHz, the three acoustic core resonances are strongly driven, coupled and phase-locked by the sequence of laser pulses.
CRIS-Team Scopus Importer:2020-11-13